Raman Spectroscopy of Nascent Soot Oxidation: Structural Analysis During Heating - De Falco, G.; Bocchicchio, S.; Commodo, M.; Minutolo, P.; D’Anna, A. (Frontiers in Energy Research, 2022)
The effect of oxidation on nascent soot particles is investigated in this work by means of Raman spectroscopy. Three different soot particle samples are produced in a lightly sooting ethylene/air laminar premixed flame and collected at different residence times. The samples are characterized by different dimension of primary particles and a different degree of aging and hence graphitization, and they are representative of the early evolution of nascent soot in flames. Oxidation of particles is induced by exposing the samples to a high temperature oxidation treatment in air over a range of temperature 25-500 °C. To this aim, a programmable heating microscope stage is used. Thermo-optical transmission (TOT) measurements are used to characterize chemical composition in terms of organic and elemental carbon content, also providing the pyrolytic carbon fraction of the organic carbon. The TOT results show that the organic fraction is constant for the three conditions. On the other hand, the pyrolytic carbon fraction decreases and the elemental carbon increases when moving from the sample composed of just-nucleated particles to the sample mostly made of mature soot particles. Raman spectroscopy reveals that the thermal oxidation treatment performed on the sample of just-nucleated particles, with the highest organic carbon content, results in a reduction of the amorphous carbon component. Conversely, the sample of mature soot, with the highest elemental carbon content, shows an increase in the amorphous carbon phase after oxidation, which is attributed to fragmentation or the formation of point defects by O2 oxidation. Finally, the thermal oxidation procedure produces a strong reduction in the photoluminescence signal detected from Raman spectra.